PERTANGGUNGJAWABAN TERHADAP TINDAK PIDANA PENYEBAR BERITA PALSU (HOAX) BERDASARKAN UNDANG-UNDANG NOMOR 19 TAHUN 2016 TENTANG PERUBAHAN ATAS UNDANG-UNDANG NOMOR 11 TAHUN 2008 TENTANG INFORMASI DAN TRANSAKSI ELEKTRONIK - Apilla Rahma Putri; Mukhlis R; Sukamarriko Andrikasmi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
In the era of globalization the rapid development and progress ofinformation technology has led to changes in human life activities in various field.The development of information technology has influenced the development ofnow forms of crime that are more modern in nature namely the rise of fake news(hoaxes). In the name of freedom netizens feel they have right over their personalaccounts. Firm action needs to be taken in the form of imposing criminal penaltieson those who carry out the dissemination in order to give a warning not to actarbitrarily on social media. On the other hand there is no need to undermine thespirit of freedom of expression in a democratic system. The purpose of writing thisthesis is : first, to find out criminal responsibility related to those who spread fakenews (hoaxes) on social media. Second, to find out who is responsible for fakenews (Hoaxes) on social media.The type of research conducted by the author is normative juridicalresearch because it makes library materials the main focus in conductingresearch. This research is descriptive, in nature namely a study that describesclearlyand in detail about a problem.From the result of research problems there are two main things thatcan be concluded. Firsty, criminal liability for perpetratpors of criminalacts of spreading fake news (Hoaxes) on social media can be heldaccountable by being imposed by two legal regulations, namely law number19 of 2016 concerning amendments to law number 11 of 2008 concerninginformation and electronic transactions in article 45A paragraph 1 and inthe criminal code in article 360. The two,Every person who spreads fakenews (Hoaxes) is obliged, such as the Ministry of Communication andInformation, which handles the initial action. If there is fake news(Hoaxes)yhat spreads, the Indonesian Police also begins to follow up on thereport fake news (Hoaxes) in the hope that the news can be known morequickly whether it is true or a Hoax.Keyword : Criminal Liability – Fake News (Hoaxes) – Social Media